Nanotube Arrays: Bioinspired Patterning with Extreme Wettability Contrast on TiO2 Nanotube Array Surface: A Versatile Platform for Biomedical Applications (Small 17/2013). Issue 17 (3rd September 2013) - Lai, Yuekun; Lin, Longxiang; Pan, Fei; Huang, Jianying; Song, Ran; Huang, Yongxia; Lin, Changjian; Fuchs, Harald; Chi, Lifeng
<x xml:space="preserve">Abstract</x> The construction of erasable and rewritable superhydrophilic–superhydrophobic patterns on novel TiO2 nanotube arrays is described by Y. K. Lai, C. J. Lin, L. F. Chi, and co‐workers on page 2945. The patterned superhydrophobic surface is an excellent 2D scaffold for site‐selective cell adhesion and reversible protein absorption, and acts as a template to deposit or grow well‐defined 3D spatially functional biomaterials (e.g., CaP, Ag, biological molecules, and drugs). Furthermore, the functional composite patterning allows specificity for SERS sensors, antibacterial agents, targeted drug delivery and cell bioassays. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>